This preview shows page 1. Sign up to view the full content.
Unformatted text preview: 1 2 mv 2 2 2 mg ( f + ) 1 2 k 2 = 0 Substituting for 1 2 mv 2 2 from above, this equation becomes 1 2 mV 2 + 2 mg f w sin 1 2 cos W = 2 mg ( f + ) + 1 2 k 2 We are given = 1 2 f and 2 = 1 3 , wherefore 2 mg ( f + ) + 1 2 k 2 = 1 3 mg w 3 2 f W + 1 2 k w 1 2 f W 2 = 1 2 mg f + 1 8 k f 2 Combining these two equations yields 1 2 mg f + 1 8 k f 2 = 1 2 mV 2 + 2 mg f w sin 1 2 cos W Solving for k , we conclude that k = 4 mg f w 4 sin 2 cos 1 + V 2 g f W...
View
Full
Document
 Spring '06
 Shiflett

Click to edit the document details